Pre-school in Brasil - Ruben Klein (Universidad Autónoma de Madrid, 2018)
This paper shows the evolution of enrolment in pre-schooland and day-care in Brazil, using data collected by National Housing Surveys conducted by IBGE and School Censuses. Using data from the Brazilian assessment (SAEB) of 2003, the paper shows a positive association between performance in mathematics and entering in pre-school or day-care. The data is controlled by a social-economical index of the students. The paper stresses that it is necessary to improve the quality of day-care and pre-school.